Encapsulation of Human Elastic Cartilage-Derived Chondrocytes in Nanostructured Fibrin-Agarose Hydrogels - Godoy-Guzman, C (Springer Verlag, 2017)
The generation of elastic cartilage substitutes for clinical use is still a challenge. In this study, we investigated the possibility of encapsulating human elastic cartilage-derived chondrocytes (HECDC) in biodegradable nanostructured fibrin-agarose hydrogels (NFAH). Viable HECDC from passage 2 were encapsulated in NFAH and maintained in culture conditions. Constructs were harvested for histochemical and immunohistochemical analyses after 1, 2, 3, 4 and 5 weeks of development ex vivo. Histological results demonstrated that it is possible to encapsulate HECDC in NFAH, and that HECDC were able to proliferate and form cells clusters expressing S-100 and vimentin. Additionally, histochemical and immunohistochemical analyses of the extracellular matrix (ECM) showed that HECDC synthetized different ECM molecules (type I and II collagen, elastic fibers and proteoglycans) in the NFAH ex vivo. In conclusion, this study suggests that NFAH can be used to generate biodegradable and biologically active constructs for cartilage tissue engineering applications. However, further cell differentiation, biomechanical and in vivo studies are still needed. © 2016, Springer-Verlag Berlin Heidelberg.